Scapular Fasciocutaneous Flap In Neck Contractures - Dr. Khurshid Ahmad (Indian Journal of Plastic Surgery)
A case where posterior neck scapular fascio cutaneous flap, as full thickness cover, for released post contracture neck is used, is presented and its merits are discussed.